Universal Measures. - Dumalin, Caroline; Garabedian, Mekhitar; Van Der Gucht, Saskia; Hendrikse, Paul; Kubat, Zeynep (Antwerp : Sint Lucas School of Arts)
Joud Toamah: 100 Days ; Liesbeth Bussche & Irma Foldényi: The Why of Diamonds Researching Jewellery, Matter, Time ; Daniel Cabral: Milestones ; Wesley Meuris & Jill Gasparina: Oasis and Boxes Green Friends / Amis Verts ; Elise Hoebeke: Personal Unit(y) ; Peter Lemmens & Annemie Vermaelen: BETAVILLE, or REVERSE ENGINEERING THE FUTURE (estimated reading time 45' 32") ; Bahia Shebab & Ruth Loos: Reading Scripts Outside Dictionaries
boek